1992
DOI: 10.1038/bjc.1992.387
|View full text |Cite
|
Sign up to set email alerts
|

Lack of prognostic significance of DNA ploidy and S phase fraction in breast cancer

Abstract: SummaryDNA Ploidy and S phase fraction (SPF) were measured in Stage I and II breast cancers from patients with at least 8 years of follow-up, to assess the prognostic significance of these data. Disaggregated sections of formalin-fixed, paraffin-embedded tumour were analysed by flow cytometry. SPF was calculated using a rectangular model of S phase, after subtraction of background debris using an exponential model. 64% of tumours were DNA aneuploid. The median SPF was 4.5% for DNA diploid, and 10.9% for DNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1
4

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 12 publications
1
12
1
4
Order By: Relevance
“…
S_q In this single-centre study of 881 patients, S-phase fraction (SPF) was shown to be a sgnifiant prognostic marker in terms of ovrll suvival (OS), rdapse-free survival (RFS) A further stimulus to publish our data came from two recent reports which failed to find a prognostic role for SPF in breast cancer (Stanton et al, 1992; Silvestini et al, 1993
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
S_q In this single-centre study of 881 patients, S-phase fraction (SPF) was shown to be a sgnifiant prognostic marker in terms of ovrll suvival (OS), rdapse-free survival (RFS) A further stimulus to publish our data came from two recent reports which failed to find a prognostic role for SPF in breast cancer (Stanton et al, 1992; Silvestini et al, 1993
…”
mentioning
confidence: 99%
“…Further tumour samples were studied for comparison of flow cytometric parameters with other tumour characteristics such as histological grade (Masters et al, 1987) and c-erb-B-2 expression (Banes et al, 1992) or for analysis of the effects of different fixation methods on flow cytometric analyses (Gilkett et al, 1990). These A further stimulus to publish our data came from two recent reports which failed to find a prognostic role for SPF in breast cancer (Stanton et al, 1992;Silvestini et al, 1993 outcome. The mean age of the patients was 55.9 (range 21-94) years.…”
mentioning
confidence: 99%
“…The finding corroborates our previous data on a large series of 308 unselected breast cancer patients [12] , in which DNA flow cytometry was found to be a predictive factor in the identification of low-and high-risk subgroups, allowing better stratification of individual patients for appropriate treatment. On the contrary, however, some previously published studies that investigated large series ( 1 300 patients) with long follow-up ( 1 5 years median) did not demonstrate the significant prognostic value of DNA flow cytometry in breast cancer [13][14][15] . Technical pitfalls relat- ed with lack of standardized procedures, different sampling sources, difficult interpretation of DNA histograms and DNA intratumoral heterogeneity limit the accuracy and reproducibility of flow cytometric data, and may explain the controversial results obtained.…”
Section: Discussionmentioning
confidence: 80%
“…However, the prognostic value of DNA parameters has been questioned (Utyerlinde et al 1989;Stanton et al 1992). A range of additional DNA histogram parameters has also been reported to yield prognostic information in breast cancer (Böcking et al 1984;Opfermann et al 1987;Stenkvist and Strande 1990).…”
Section: Introductionmentioning
confidence: 96%